The Singapore Green Plan 2030: occupational health hazards in the Singapore green economy - Wei Xiang Lim; Mei Ling Licia Tan; Tzu Li Sylvia Teo; Wee Hoe Gan; Shiu Hong Joshua Wong (Singapore Medical Journal)
The Singapore Green Plan 2030 was released by the Singapore government to set targets for sustainability by 2030. The adoption of novel technologies, processes and substances creates new jobs, and such developments bring about new challenges and risks for both employers and workers. Beyond emerging hazards, traditional hazards still remain, but they may take on new forms through new work processes. This review aims to provide an overview of the potential occupational health issues we may encounter or anticipate in these key sectors: solar energy, waste management and recycling, green buildings, electric vehicles and battery recycling, and sustainable fuels. While existing Occupational Safety and Health regulations in Singapore serve as a foundation, there may be gaps in addressing the specific hazards and risks associated with green jobs. In this review, we propose and outline possible approaches to the protection of worker safety and health.